Historische Lexikographie zwischen Tradition und Innovation - Lobenstein-Reichmann, Anja; Müller, Peter O. (Studia linguistica Germanica, 2016)
"For some time, historical lexicography has been suspended between the demands of traditional philology, modern metalexicography, and technical innovation. The essays in this compilation volume reflect the challenges associated with these demands as well as ways to overcome them. They also reveal that historical lexicography is conceptually and institutionally capable of continuously re-inventing itself."--
Literaturangaben
Keywords: Aufsatzsammlung; Historische Lexikografie; Deutsch